Measurement of Human Papillomavirus-Specific Antibodies Using a Pseudovirion-Based ELISA Method - Toh, Zheng Quan; He, Laura; Chen, Catherine; Huang, Angela; Russell, Fiona M.; Garland, Suzanne M.; Reyburn, Rita; Ratu, Tupou; Tuivaga, Evelyn; Frazer, Ian H.; Mulholland, E. Kim; Licciardi, Paul V. (Frontiers in Immunology, 2020)
Human papillomavirus (HPV) vaccines are safe and effective in preventing HPV infection and cervical precancers. Neutralising antibodies are thought to be the primary mechanism of protection for HPV vaccines, although the exact level required for protection has not been identified. Three common serological assays used in clinical trials to measure HPV antibodies are HPV pseudovirion-based neutralisation assay (PBNA), competitive or total Luminex immunoassays (cLIA or LIA) and VLP-based enzyme linked immunosorbent assays (ELISA). While PBNA is the gold-standard for measuring neutralising antibodies (NAb), it is labour intensive. Luminex immunoassay and VLP-ELISA are rapid and high throughput, but their reagents and equipment can be difficult to source. Nevertheless, data generated from these assays generally correlate well with PBNA. Here, we described a simplified high-throughput PsV-based ELISA for HPV antibody measurement, to circumvent some of the limitations of existing assays. Using this assay, we were able to differentiate HPV-specific IgG and IgM, and found a strong correlation between HPV-specific IgG and NAb levels, as previously determined by PBNA. This assay platform is simpler and less time-consuming than PBNA. In addition, the materials can be readily produced and obtained commercially. This assay can be used as an alternative method to measure HPV antibodies.